Pulmonary Function Responses During Inspiratory Muscle Training in Patients with Chronic Heart Failure: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Georgios Mitsiou; Irini Patsaki; Afrodite Evangelodimou; Eirini Grammatopoulou (Healthcare, 2026)
Background: Exercise intolerance is a common symptom in patients with chronic heart failure (CHF) and is often associated with reduced pulmonary function. Breathing exercise, including inspiratory muscle training (IMT) has been shown to alleviate respiratory symptoms in patients with pulmonary and cardiac disease. The purpose of this systematic review is to assess the impact of IMT on maximal inspiratory pressure (Pimax), diaphragm thickness, functional vital capacity (FVC), dyspnea and maximum oxygen uptake (VO2peak) in patients with CHF. Methods: Database research was conducted (PubMed, EMBASE, Cochrane Library of Controlled Trials) by using an appropriate algorithm to indicate the IMT effect on pulmonary function studies. Eligibility criteria included pulmonary function measurements following IMT in patients with CHF. A continuous random effect model (PROSPERO-CRD420261360295) was used to calculate standard mean differences (Std.MD) in all outcomes (between an experimental and control group). Results: A total of 395 participants (13 randomized controlled trials) were identified. More studies indicate improvement in Pimax after IMT (Pimax: Std.MD: 1.07; 95%CI, 0.72–1.42; p < 0.00001). Functional vital capacity (Std.MD, 0.41; 95%CI, 0.03–0.79; p = 0.03) and dyspnea (Std.MD, 1.11; 95%CI, 0.57–1.66; p < 0.0001) were also improved. Moreover, VO2peak assessed by cardiopulmonary exercise testing before and after IMT showed statistical significance (VO2peak: Std.MD: 0.86; 95%CI, 0.06–1.66; p = 0.04) in trained patients with CHF compared to controls. Conclusions: The meta-analysis indicates that isolated IMT performed either as short- to medium-term intervention (4 to 8 weeks) with moderate to high intensity (40 to 90% Pimax) or long-term program (8 to 12 weeks) with low intensity (30% Pimax) promotes pulmonary function and metabolic responses. More studies are required to examine the impact of IMT on diaphragm thickness in patients with chronic heart failure.